Causes of Missed Nursing Care During COVID-19 Pandemic: A Qualitative Study in Iran - Safdari, Ali; Rassouli, Maryam; Jafarizadeh, Raana; Khademi, Fatemeh; Barasteh, Salman (Frontiers in Public Health, 2022)
Background The unpredictable and variable nature of COVID-19 and the lack of healthcare resources has led to inadequate care for patients. This study aimed to explain the causes of missed nursing care during the COVID-19 pandemic from the perspective of Iranian nurses. Method This qualitative study was conducted using semi-structured interviews with 14 nurses caring for patients with COVID-19 in three hospitals in Iran. Sampling was performed by the purposive method. Data were analyzed using the conventional content analysis method. The interviews were first recorded and transcribed, and then the data were analyzed using the Elo and Kyngas method. Data management was done with MAXQDA software version 10. To achieve trustworthiness, the criteria presented by Lincoln and Guba were used. Findings A total of 14 nurses participated in the study. The mean age of participants was 31.85 ± 4.95 years, and the mean number of years of work experience was 7.71 ± 4.44. Eleven participants were women. Among all participants, nine had a bachelor's degree and five had a master's degree. Four nurses had fixed shifts, while ten nurses had rotating shifts. The causes of missed nursing care were categorized into 4 groups. The category “unfulfilled care” comprised the reasons for forgetting care, neglecting care, arbitrary elimination of care, and compulsory elimination of care. The category of “care at improper time” consisted of interference of the care in patients' daily activities and interference with other healthcare providers' activities. The “incomplete cares” category comprised failure to complete the care period in hospital, interruption in care, and discontinuance of care after patient discharge. The last category, “incorrect care,” consisted of providing care regardless of the nursing process, providing care by unqualified professionals, and providing trial-and-error care. Conclusion This study illustrates an understanding of the causes of missed nursing care during the COVID-19 pandemic from the perspective of nurses. The increasing demand for care caused by the pandemic and problems in the work environment has led to the failure of nurses to provide complete, correct care and sometimes miss parts of care to patients. Therefore, nursing policymakers and managers should develop and implement appropriate care protocols and instructions to minimize missed nursing care.